Educação contextualizada e convivência com o semiárido brasileiro: perspectivas para o ensino de ciências - Figueiredo, Gustavo de Alencar (2017)
This paper aims to examine the limitations and challenges that must be overcome by these teachers‗ pedagogical practice, as well as the curriculum of schools in the Brazilian semiarid, to the consolidation of a science education that brings with proposal of a contextual education and committed to the sustainable alternatives for living in this region. This study also sought to reflect on the politics of education and development for the Brazilian Semiarid having as foundation which has been and is being done to implement this proposal of Education, arguing how it can deconstruct the discourse that historically constructed subjectivities about semiarid on the national scene, denying their true potential and shared throughout its existence by people who live along its entire length knowledge. Speeches that propagated as truths which were the relations of power-knowledge existing in the society. The context was the pedagogical principle taken as one of the references used in the analysis of the science curriculum in Teaching Fundamental. This study was based on the perspective of qualitative research being conducted in four (04) local schools at Cajazeiras - PB. Eight (08) teachers of Natural Sciences of the final years of Elementary School participated answering questions that seek to investigate the existence, or not, in relation to their teaching as a contextualized education in perspective living as semiarid. For this case, it is believed that the "thick description", in the perspective of interpretive anthropology of Clifford Gleertz and Edgar Morin‘s Complex Thought present themselves as important methods for understanding the concepts put forward by / the screen in search of the protagonists. It was demonstrated they have difficulty in relating the content included in the science curriculum for primary education, with characteristic phenomena (such as drought) observed in the Brazilian Semiarid. The results show that the strengthening of a policy of initial and continuing training of science teachers who articulate the inclusion of a contextualized education for the Semiarid and that values cultural diversity in this environment is necessary. The analysis signals also to the ignorance of the Law 10,639/2003 which guides the know-how teaching concerning education for ethnic-racial relations and checks the decontextualized treatment of the contents taught in the curriculum component of natural sciences, which makes it difficult for students reflect on the true role of science in their lives, so they can understand it as part of a culture produced by men and women, as well as their relevance in the understanding of natural phenomena observed in the world around them.